Properties of foam concrete with expanded Polystyrene - Harold, Mamat (Universiti Malaysia Sarawak (UNIMAS), 2010)
Most study done on the foam concrete in the past were on the properties of foam concrete with replacement of fly ash, silica fume and the use of admixtures. This project is done to study the influence of the expanded polystyrene (EPS) as fine aggregate replacement on the mechanical and durability properties of foam concrete. The effect of various tham volumes on foam concrete with EPS is also studied. Nine samples of foam concrete containing various percentages of EPS replacement and foam volume of 30`Y° and 50% were prepared and studied. The EPS replacements range from 0% to 50% by volume of tine aggregate (sand). The study shows that the 28 days strength of team concrete containing EPS is decreases with the increasing of EPS replacement. The failure mode of foam concrete with EPS was also observed to he gradual and not brittle as in normal concrete. However, the flexural-compressive strength ratio increased with the increase percentage of EPS replacement. The study also shows that EPS used in foam concrete can reduce the water absorption as compared to the conventional foam concrete. When compared among foam concrete containing EPS replacement only, the water absorption increased with volume of FPS replacement.